The effects of carbamazepine and levetiracetam on serum prothrombin time (PT), activated partial thromboplastin time (APTT), and D-dimer (D-D) levels and fibrinogen (FIB): serum prothrombin time (PT), activated partial thromboplastin time (APTT), and D-dimer (D-D) levels and fibrinogen (FIB) - Bian, Guanji (Journal of Medical Biochemistry, 2025)
Introduction: epilepsy is a common neurological disorder, so exploring its treatment programs is of high significance. In this content, this work was developed to compare the effects of monotherapy with Carbamazepine (CBZ) and Levetiracetam (LEV) on coagulation factors and disease control in patients with partial-onset epilepsy (POE). Materials and Methods: in this work, 89 patients with POE diagnosed and treated at our hospital from January 2023 to January 2024 were enrolled. The patients were rolled into the CBZ group and the LEV group. Blood coagulation parameters were measured before and after treatment, and the frequency and severity of epileptic seizures were recorded for patients in different groups. Results: regarding coagulation factors, in the CBZ group, prothrombin time (PT), activated partial thromboplastin time (APTT), and D-dimer (D-D) levels at 1, 3, and 6 months after treatment were sharply lower in contrast to the pre-treatment levels, while changes in the LEV group were not obvious. Meanwhile, the fibrinogen (FIB) content after treatment was decreased in both groups. Furthermore, the frequency of epileptic seizures in all patients was reduced greatly after treatment, and difference in the control rate of frequency of epileptic seizure was not greatly different for patients in different groups. Conclusion: CBZ may increase the risk of coagulation abnormalities, but it was highly effective in controlling epileptic seizures. However, LEV had a smaller impact on coagulation and exhibited similar effect in controlling epileptic seizures.
Keywords: serum prothrombin time (PT), activated partial thromboplastin time (APTT), and D-dimer (D-D) levels and fibrinogen (FIB)